Evaluating the effect of ownership status on hospital quality: The key role of innovative procedures - Laurent Gobillon; Carine Milcent (Institute for the Study of Labor (IZA), 2012)
Mortality differences between university, non-teaching public and for-profit hospitals are investigated using a French exhaustive administrative dataset on patients admitted for heart attack. Our results show that innovative procedures play a key role in explaining the effect of ownership status on hospital quality. When age, sex, diagnoses and co-morbidities are held constant, the mortality rates in for-profit and university hospitals are similar, but they are lower than in public non-teaching hospitals. When additionally controlling for innovative procedures, the mortality rate is higher in for-profit hospitals than in the two groups of public hospitals. This suggests that the quality of care in for-profit hospitals relies on innovative procedures and that, after controlling for case-mix and innovative treatments, there is a better quality of care in public hospitals.
Keywords: I12; I18; 330; hospital performance; innovative procedures; stratified duration model; hospital quality; Krankenhaus; Unternehmenserfolg; Eigentümerstruktur; Innovation; Dienstleistungsqualität; Öffentliches Unternehmen; Frankreich